A review of benchmarking as a tool for continuous improvement - Baba Md Deros,; Sha’ri Mohd Yusof ,; Azhari Md Salleh, (Penerbit ukm, 2005)
This paper presents a general review of benchmarking studies in the overall context. It begins with a description of the concepts relating to benchmarking, the history, the stages of development and definitions. It further discusses the concept of benchmarking relating to methodology, classifications and purposes, issues and problems, benefits, in implementing benchmarking. In addition, it briefly discusses benchmarking relationship with other improvement and change management programs. The paper culminates with a summary on the benchmarking tool